2006
DOI: 10.1291/hypres.29.397
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Spot Urine Method in Evaluating Daily Salt Intake in Hypertensive Patients Taking Oral Antihypertensive Drugs

Abstract: Kawasaki et al. developed a spot urine method (SUM) for evaluating daily salt intake using one pre-breakfast sample obtained after initial voiding upon arising. Their subjects were healthy persons who were not taking any regular medications. To determine whether SUM can be successfully used for patients taking antihypertensive drugs, we estimated daily salt intake in 73 hypertensive patients by SUM and by a food consumption method (FCM) when they were at home, and also by SUM in the hospital with a defined int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 27 publications
2
38
0
2
Order By: Relevance
“…*Cut points for the quartiles of daily salt intake were 8, 10 and 12 g. Low daily salt intake and albuminuria K Sakabe et al values obtained from the spot urine method correlated highly with those obtained from 24-h urinary sodium excretion, 19 and the usefulness of the spot urine method has been confirmed in population studies 20 and in hypertensive patients. 21 We speculate that excessive dietary salt restriction leads to increased angiotensin II and aldosterone levels, chiefly via an increase in plasma renin activity. Protein consumption is also known to be a critical factor in albuminuria.…”
Section: Discussionmentioning
confidence: 90%
“…*Cut points for the quartiles of daily salt intake were 8, 10 and 12 g. Low daily salt intake and albuminuria K Sakabe et al values obtained from the spot urine method correlated highly with those obtained from 24-h urinary sodium excretion, 19 and the usefulness of the spot urine method has been confirmed in population studies 20 and in hypertensive patients. 21 We speculate that excessive dietary salt restriction leads to increased angiotensin II and aldosterone levels, chiefly via an increase in plasma renin activity. Protein consumption is also known to be a critical factor in albuminuria.…”
Section: Discussionmentioning
confidence: 90%
“…However, this finding should be carefully analyzed, because the method for urine collection was different in previous studies. It is worth to mention that the subgroups that mostly benefitted from the reduction in salt consumption, such as hypertensive people, still consume much more than the recommended amount 29,31 . Similarly to what was observed in other studies 12,13,[23][24][25] , we observed moderate correlation between the salt intake estimated by casual urine and the consumption measured in 24 hours.…”
Section: Discussionmentioning
confidence: 99%
“…These findings agreed with our previous results. 13 Chronic administration of diuretics was considered most likely to interfere with the SMU method because these drugs have the strongest natriuretic effect among or the 24-h urine collection method (closed columns). There were no significant differences in the estimated salt intake between the two methods (Wilcoxon's signed-rank test).…”
Section: Discussionmentioning
confidence: 99%
“…The usefulness of the SMU method has been confirmed in population studies 5,11,12 and in hypertensive patients. 13 Although the posture that should be adopted for the SMU method was not specified by the original authors, 10 posture is known to affect the urinary sodium:creatinine ratio 14,15 and could possibly influence the estimation of daily salt intake by this method. Therefore, this study was designed to assess the effect of posture on the estimation of daily salt intake by the SMU method compared with the method of 24-h collection in hospitalized patients with hypertension on a saltrestricted diet.…”
Section: Introductionmentioning
confidence: 99%